Salmon testes meal as a functional feed additive in fish meal and plant protein‐based diets for rainbow trout (Oncorhynchus mykiss Walbaum) and Nile tilapia (Oreochromis niloticus L.) fry. (29th October 2013) - Lee, Kyeong‐Jun; Rahimnejad, Samad; Powell, Madison S; Barrows, Frederick T; Smiley, Scott; Bechtel, Peter J; Hardy, Ronald W
Abstract Fishery processing by‐products are a large resource from which to produce fishmeal and other products for a variety of uses. In this study, testes meal (TM) produced from pink salmon processing by‐product was evaluated as a functional ingredient in aquafeeds. Nile tilapia and rainbow trout fry were fed five isonitrogenous and isoenergetic experimental diets for 4 and 9 weeks respectively. Two diets were fishmeal‐based (FM) and three were plant protein‐based (PP). Salmon TM was added to the FM and PP diets at 7% to replace 20% of fishmeal protein (FMTM and PPTM respectively). An additional control diet was prepared in which fishmeal was added to the PP diet to supply an equivalent amount of protein as supplied by TM (PPFM). Inclusion of TM in both the FM‐ and PP‐based diets resulted in higher final body weights, although differences were only significant between rainbow trout fed FM or FMTM diets. Similar differences were calculated for other indices of fish performance, e.g. specific growth rate, feed conversion ratio, protein efficiency ratio and protein retention efficiency. Feed intake was significantly higher for fish fed FMTM compared with FM in rainbow trout. For tilapia, final weights were numerically higher, but not significantly different for fish fed diets containing TM compared with non‐TM diets (FM vs. FMTM; PP vs. PPTM). Performance of trout or tilapia fed the PPFM diet did not increase compared with the PP diet. The results indicate that TM addition to both FM and PP diets increased feed intake and also increased metabolic efficiency, demonstrating that TM can be a functional ingredient in aquafeeds.